Mutational analysis of isoform selectivity and conformational equilibria in protein kinase inhibition - Alexander, LT (2015)
Deregulation of protein kinases is associated with many diseases making them important targets for therapeutic intervention. Kinases can switch between active and inactive conformations that can be targeted by type 1 or type 2 inhibitors respectively. One of the most relevant conformational switches is the ‘in’ and ‘out’ movement of the ATP/Mg2+ binding motif DFG. Factors modulating the conformational equilibria such as the residue environment of regulatory motifs remain poorly understood despite their importance for drug discovery. In this thesis, the first model system tested the hypothesis that accessibility of the DFG-out conformation is restricted by the energetic cost of transition between the in and out states. CDK2 was chosen as a target that was thought to have an inaccessible DFG-out conformation, and several point mutations were introduced to promote this conformational transition. Detailed biochemical and biophysical characterisation illustrated that the mutants bound type 2 inhibitors more potently than the wild type. In addition, the wild-type CDK2 was shown to bind type 2 inhibitors in the absence, but not in the presence, of cyclin. The first known CDK2 co-crystal structure in the DFG-out conformation was solved, opening the door to a new class of CDK2 inhibitors. In the second project, site-directed mutagenesis was used to explore the residues determining inhibitor selectivity between PIM1 and PIM2. Evaluation of ligand binding to the variants and comparison of PIM1 and PIM2 crystal structures showed that flexibility of the phosphate-binding loop was the dominant factor determining the differences in their affinities for ATP and small molecule inhibitors. These studies illustrate that residues contributing to kinase conformational equilibria can be just as important for inhibitor binding as contact residues formed in the ligand complex.